Web-Based Work Practice Report Guidance Management Information System in Schools Using the Waterfall Method - Markani; Juli Wanda; Listia Utami; Tamra; Liam Johnson (Ceddi Journal of Education, 2024)
In the current digital era, managing guidance on Field Work Practice (PKL) reports at SMKN 5 Takalar requires a more structured and efficient system. Conventional methods often lead to ambiguity in communication and scheduling, as well as a lack of good documentation. This research aims to develop a web-based PKL report guidance management information system at SMKN 5 Takalar using the Waterfall method, which includes the stages of needs analysis, design, implementation, testing, and maintenance. This system is designed to overcome the problems of lack of clarity in communication, scheduling, and lack of good documentation in guidance on PKL reports. The research results show that this system is able to make the guidance process more structured with interpretation results of 94%, well documented, and efficient. The features provided facilitate communication between students and teachers, track guidance progress, and improve the quality of PKL reports. Apart from that, this system also optimizes the arrangement of meeting schedules between supervising teachers and students, making it more efficient and structured. Thus, it is hoped that this web-based PKL reports guidance management information system can be an effective solution to overcome the problems faced in the PKL guidance process at SMKN 5 Takalar.